Virtual reality and stroke rehabilitation: a mixed reality simulation of an everyday task - Hilton, David (2008)
This thesis is about the process of designing a computer simulation as a treatment tool for stroke rehabilitation. A stroke is a debilitating disease that is characterised by focal neural damage usually leading to physical and cognitive impairments. These impairments may severely compromise the stroke survivor's ability to perform everyday tasks of self-care such as dressing, washing and preparing meals. Safety issues are also an important consideration for the rehabilitation of the stroke survivor. Some everyday tasks can be hazardous, particularly when electrical equipment or hot liquids are involved. Computer simulations are gaining interest as a tool for stroke rehabilitation because they offer a means to replicate assessments and everyday tasks within ecologically valid environments. Training the motor skills required to perform everyday tasks together with the cognitive component of the activity is desirable however this is not always achieved due to the limitations of the human computer interface. These limitations are addressed by a simulation that is presented in this thesis. Stakeholders in stroke care contributed to the design and development of the simulation in order to ensure that it conformed to their requirements. The development culminated in a mixed reality system with a unique method of interaction in which real household objects were monitored by various electronic sensing technologies. The purpose of controlling the computer simulation using real objects was to encourage users to practice an everyday task (making a hot drink) using naturalistic upper limb movement whilst performing the task in a safe and controlled environment. The role of the computer was to monitor and score user's progress, and to intervene with prompts and demonstrations as required. The system was installed on a hospital stroke unit and tested by patients, something that had previously not been achieved. It was found to be acceptable and usable as a means of practicing making a hot drink. The system design, limitations and recommendations for future developments are discussed.